A cinematografia de Lucia Murat: entre suas experiências e os embates em torno da memória da ditadura civil-militar no Brasil - Silva, Cleonice Elias da (2020)
This doctoral research examines the relationships between history, cinema and memory. To this purpose, a study was made based on the films of Lucia Murat Que Bom Te Ver Viva (1989), Quase Dois Irmãos (2005), Uma Longa Viagem (2011) and A Memória Que Me Contam (2013), highlighting the speeches of memory about the civil-military dictatorship that they reverberate in our society. We considered the aspects of the filmmaker's experiences and memories present in her films in a dimension marked by subjectivities which play an important political role in the current disputes and debates regarding the memories of the civil-military dictatorship. The films cited with specific characteristics corroborate the conjuncture of the right to memory and truth, with the denunciations of human rights violations promoted during the military governments, and in the scenario of struggles to not forgetting them. For the development of reflections, we based on Walter Benjamin's (1994) main assumptions about experience, and pioneers studies about memory such as Halbwachs (1990), Nora (1993), Pollak (1989, 1992), Le Goff (2013), Todorov (2002), Jelín (2002a), as well as those by Rosenstone (1997, 2010), Morettin (2003) and Kornis (1992) on History and Film